What tools are available to assess climate and environmental health impacts on perinatal families with an equity lens? A rapid review of the Canadian context - Alysha T. Jones; Émilie Tremblay; Anne-Lise Costeux; Jacqueline Avanthay Strus; Adrienne Barcket (BMC, 2024)
Abstract Objectives This rapid review is designed to identify existing tools in the Canadian literature that assess the impacts of climate change on the health of perinatal families, particularly those who are equity-denied. Addressing the needs of equity-denied perinatal populations in the face of climate change is crucial to promoting equitable and inclusive perinatal care in Canada. Methods Rapid review methodology was selected to provide evidence in a timely and cost-effective manner. PubMed/MEDLINE and gray literature (Google and Google Scholar) were searched for English and French papers published from 2013 onward. The original research question, focused on climate change and health, yielded very few relevant results. Therefore, the search was broadened to include environmental health. Garrity et al.'s (J Clin Epidemiol 130:13-22, 2021) nine-stage process was used to identify 11 relevant papers, extract the relevant data, and complete the narrative synthesis. Synthesis. This review revealed a significant lack of tools for comprehensively assessing climate-health impacts on perinatal families and equity-denied perinatal families. While Canadian perinatal health screenings focus on equity via indicators of several social determinants of health (e.g., income, social support), they largely omit climate considerations. Environmental health factors are more commonly included but remain minimal. Conclusion Climate-health screening tools are lacking yet needed in routine perinatal healthcare. Given the seriousness of climate change, urgent engagement of health systems and healthcare workers is essential to help mitigate and adapt to climate-health challenges, particularly for perinatal families experiencing health inequities.